Testing the role of action and inaction anticipated regret on intentions and behaviour. (25th March 2016) - Sandberg, Tracy; Hutter, Russell; Richetin, Juliette; Conner, Mark
Abstract : Anticipated regret (AR) has been suggested as a useful addition to the theory of planned behaviour (TPB) that captures affective influences. However, previous research has generally (1) assessed the impact of AR in relation to one behaviour (action or inaction) when considering TPB variables in relation to the alternative behaviour, (2) not controlled for affective attitudes or past behaviour, and (3) examined only one or two behaviours. In two studies across several behaviours, the present research showed that even when controlling for affective attitudes, past behaviour, and other TPB variables towards action, action and inaction AR each added to the prediction of intentions across multiple behaviours. The two studies also showed that inaction regret was generally the stronger predictor, although action regret was important for some types of behaviour. Implications and issues for further research are discussed.